Suonatori di AULOS, eccessi nel cibo e musicoterapia: a proposito di Hippon. Frr. 4, *4A, 78, 102, 118, *151A W.2 E FR. 153 DG - Anika Nicolosi (Exemplaria Classica, 2021)
In Hipponax’s fragments we find the name of three musicians: Babys, Cicon and Codalus (frr. 4, *4a, 78, 118 W.2 and 153 Dg.). As we know from Athenaeus (14.624a-b), they were Phrygian slaves and also magicians, and thanks to their ability, they could restore people to health. This paper reviews these fragments with two objectives in particular: first of all, to suggest a new interpretation of fr. 102 W.2, where the poet probably alludes to a musical therapy for a glutton; then, to provide a better explanation of fr. *151a W.2, thanks to a comparison with fr. 118 W.2 where Cicon sings the nomos of Codalus. The fragment not only alludes to a glutton, but refers to a specific type of melos that can help someone to cure his gluttony.